FEMINISME DALAM NOVEL GURU AINI KARYA ANDREA HIRATA - Hendrik Furqon; Yessy Soniatin; Vira Nanda Atikah; Zakiyatut Darojah (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe (1) the structure of the novel Guru Aini by Andrea Hirata (2) the feminist aspects in the novel Guru Aini by Andrea Hirata, namely: (3) the educational value in the novel Guru Aini by Andrea Hirata. This research uses descriptive qualitative research. The subject of this research is the novel Guru Aini by Andrea Hirata in 2020. This research focuses on issues related to feminism and the value of education. The data were analyzed using a qualitative descriptive technique, a research procedure with the results of the description data presented in the form of the author's speech in the novel Guru Aini by Andrea Hirata. Data collection techniques were carried out by listening and note-taking techniques. The results of the study show as aspects of feminism in the novel Guru Aini by Andrea Hirata, namely (a) the position of women; (b) the purpose of women's lives; (c) the behavior and character of the female characters; (d) the establishment of female characters and (e) the role of men in supporting feminism.